The Relation between Stock Returns and Accounting Earnings Given Alternative Information - Lipe, Robert (The Accounting Review, 1990)
[This paper examines the relation between stock returns and accounting earnings under the assumption that the market observes current-period information other than earnings. This assumption is motivated by existing empirical evidence that stock returns lead accounting earnings. The analysis shows that the returns-earnings relation depends on the relative ability of earnings versus alternative information to predict future earnings as well as the time-series persistence of earnings. Assuming that the researcher does not observe the alternative information, the earnings response coefficient should be increasing both in the ability of past earnings to predict future earnings and in earnings persistence. The variance of stock price changes during the announcement of earnings should be decreasing in predictability and increasing in persistence. Empirical tests of these four hypotheses are generally consistent with the theory. Also discussed is how the assumption of alternative information may be useful in examining the information environment hypothesis, in assessing ad hoc methods of reducing measurement error bias, and in formulating how economic earnings differ from accounting earnings.]